Feeding and Eating Disorder and Risk of Subsequent Neurodevelopmental Disorders: A Population-Based Cohort Study - Shan, Hongyun; Li, Fei; Zhang, Jun; Wang, Hui; Li, Jiong (Frontiers in Pediatrics, 2021)
Background: There are limited data concerning the long-term mental health of children with feeding and eating disorders (FED). We aimed to investigate whether children with FED are at greater risks of developing emotional/behavioral disorders with onset usually during childhood, attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and intellectual disability (ID). Methods: We conducted a population-based cohort study, including all singleton births in Denmark from January 1, 1995 to December 31, 2015. For each child diagnosed with FED, 10 age- and sex-matched controls who did not meet the criteria for FED were randomly selected from the general population. Associations were estimated with Cox regression modes adjusting for other perinatal and maternal factors, and sibling analyses were performed for controlling potential confounding by shared familial (genetic or environmental) factors. Results: Of the 1 256 989 individuals in the cohort, there were 1967 (53.4% girls) children diagnosed with FED. Children with FED had higher risks for clinically diagnosed emotional/behavioral disorders with onset usually in childhood (hazard ratio [HR], 2.78; 95% CI, 2.34-3.31), ADHD (HR, 1.74; 95% CI, 1.33-2.26), ASD (HR, 3.05; 95% CI, 2.36-3.94), and ID (HR, 6.38; 95% CI, 4.48-9.11), compared with matched controls. Girls with FED are at greater risks for emotional/behavioral disorders an ID, but not ADHD and ASD. Alike, in sibling analysis, increased rates are also observed for other neurodevelopmental disorders, but not for ADHD. Conclusion: Children with FED are associated with substantially increased risks of emotional/behavioral disorders, ADHD, ASD, and ID. This study highlights the importance of carefully monitoring neurodevelopmental disorders in children with FED.